Traumatic amputation: Healing the acute lawn mower injury- a case report - Amar Chandra, DPM; Ian Barron, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases, 2022)
Background: An estimated 84,944 lawn mower injuries occur annually in the United States, of those 16.2% involving the lower extremity (Harris et al., 2018).1 Often, a significant soft tissue deficit is present leaving limited reconstructive options available to the surgeon or wound care provider. Split-thickness skin graft (STSG) has long been considered the mainstay for treatment of large skin defects caused by traumatic wounds. Issues related to graft loss, scar contracture, loss of elasticity, adhesions to tendons and unfavorable aesthetic results are regarded as limitations of skin grafting alone (Ünal et al., 2005).2 As a result, acellular dermal matrices have seen an increase in usage due to their potential to overcome these limitations (Park et al., 2014).3